1999
DOI: 10.1055/s-1999-2865
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Synthesis: From Glycobiological Tools to Tailor-made Catalysts

Abstract: Abstract:The synthesis of pure, well-defined glycoproteins is essential to the study of the host of biological processes that they mediate. The use of a combined site-directed mutagenesis and chemical modification strategy allows the site-selective synthesis of homogenous glycoproteins, the determination of precise structureactivity relationships and the design of new synthetic catalysts. This general and powerful method is reviewed in the context of existing preparative techniques and the wide-ranging applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…Among protein conjugates involved in a variety of inter‐cell communication events, glycoproteins are of special importance 15. The type and the position of carbohydrate moieties determine protein folding, receptor binding, intercellular transport, microbial virulence and host immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Among protein conjugates involved in a variety of inter‐cell communication events, glycoproteins are of special importance 15. The type and the position of carbohydrate moieties determine protein folding, receptor binding, intercellular transport, microbial virulence and host immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…To address this need for homogeneous glycoproteins, we have been working to develop new methods for the synthesis of glycopeptide mimetics. , Ideally, the designed analogues should be more easily generated than the corresponding native structures yet possess the desired biological activity. Mindful of the importance of the core GalNAc(α1- O )Ser/Thr for establishing proper organization of the glycopeptide backbone, we sought to preserve this structural element.…”
Section: Introductionmentioning
confidence: 99%
“…Benzyl ether (2) and fluorinated benzyl ethers (3)(4)(5)(6)(7) were synthesized by the reaction of methyl-α-Dmannopyronoside (1) with various benzyl bromides using Williamson ether synthesis method. The spectral analysis showed that the methylene carbons of the fluorinated benzyl ethers showed a significant shift to a high field region compared to the methylene carbons of non-fluorinated benzyl ether in the 13 C NMR spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Oligosaccharides have exhibited important role in cell-cell interactions, which has had several positive implications. [1][2][3][4][5] The key reaction involved in the synthesis of oligosaccharides is a bond formation between the anomeric center of a saccharide and a hydroxyl group from another sugar molecule. In order to synthesize oligosaccharides from monosaccharide units, the hydroxyl groups present in the monosaccharides have to be protected by the suitable protecting groups.…”
Section: Introductionmentioning
confidence: 99%